Strategic Operations Management - Brown, Steve, 1957- (Amsterdam ; London : Elsevier Butterworth-Heinemann, 2005)
This text combines four themes: strategy, services, innovation and management of relationships, both in the supply chain and with other players. Mini case studies are used to supplement the text.
Previous ed.: Oxford: Butterworth-Heinemann, 2000.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Production management; Strategic planning